产地、物种及加工工艺对油茶籽油中的微量元素 及重金属含量的影响Effects of origins,species and processing technology on contents of trace elements and heavy metals in oil-tea camellia seed oil - 刘海，王进，许杰，陈瑶，缪明胜，郭少海 LIU Hai, WANG Jin, XU Jie, CHEN Yao, MIAO Mingsheng, GUO Shaohai (Zhongguo youzhi, 2022)
以贵州不同产地及物种的油茶籽为原料，分别采用烘制和炒制对其进行预处理后压榨制油，并对油茶饼进行二次压榨制油，对不同预处理及不同压榨阶段油茶籽油的微量元素及重金属含量进行分析。结果表明：不同产地和物种的油茶籽油的微量元素及重金属含量存在不同程度的差异，形成不同品质特征的油茶籽油；与烘制预处理相比，炒制可以显著提升油茶籽油中锰、铁、铜含量（P＜0.05），但同时增加油茶籽油中的重金属含量；不同压榨阶段油茶籽油的微量元素含量具有显著差异（P＜0.05），二次压榨可使油茶籽油中的锰和铁含量显著增加（P＜0.05），且蒸制处理可以提升二榨油茶籽油中的微量元素含量；相关性分析显示，不同微量元素及重金属含量之间具有不同程度的相关性，锰和锌、铅有极显著的负相关性，锌和铅有极显著的正相关性，镍和铬有极显著的正相关性。The oil-tea camellia seeds from different origins and species in Guizhou were pretreated by roasting and frying, and pressed by hydraulic press to produce oil. The oil-tea camellia seed cake was pressed secondly to produce oil. The contents of trace elements and heavy metals in oil-tea camellia seed oil prepared by different pretreatments and in different pressing stages were determined. The results showed that the contents of trace elements and heavy metals in oil-tea camellia seed oil from different origins and species were different in varying degrees, and the oil-tea camellia seed oil had different quality characteristics. Compared with roasting, the contents of manganese, iron and copper in oil-tea camellia seed oil by frying significantly increased (P＜0.05), and the heavy metal content in oil-tea camellia seed oil increased too. The contents of trace elements in oil-tea camellia seed oil in different pressing stages had significant differences (P＜0.05). The contents of manganese and iron in oil-tea camellia seed oil increased significantly by twice pressing (P＜0.05), and steaming treatment could increase the content of trace elements in oil-tea camellia seed oil produced by secondary pressing. The related analysis showed that there were correlations in different degrees between trace elements and heavy metals. Among manganese and zinc, lead, they had very significantly negative correlations, zinc and lead had a very significantly positive correlation, and nickel and chromium had a very significantly positive correlation.